Teaching Speaking Using Picture Series in Instagram to Tenth Graders at SMK PGRI 2 Sidoarjo - Nur Soffi Sampieni; Sulistyaningsih Sulistyaningsih; Esther Hesturini (PGRI Provinsi Jawa Timur, 2022)
The objective of the study was to describe the teacher’s implementation in Teaching Speaking Using Picture Series in Instagram, and to describe The Students’ Response on the Teaching Speaking Using Picture Series in Instagram.This study used descriptive qualitative method. The data were collected from the tenth graders at SMK PGRI 2 SIDOARJO, class X RPL. The data collecting technique used instruments observation checklist and questionnaire. The finding of teaching speaking using picture series in Instagram were: Firstly, the teacher gave the stimulus of the material, explained the descriptive text, gave questions to the students to check the students understanding on descriptive text, made five groups, gave the students the pictures series of Instagram. Then, the teacher asked the students to discuss with their groups about desribing the picture series given by the teacher. At last, each group had to describe the pictures series in Instagram in front of the class by their own words. The teacher gave feedback, and revied the material to the students. Students’ responses showed that almost all the students gave responses to the answer “YES” with total numbers of 281 or 83% and answer “NO” with a total numbers of 59 or 17%. The data on the diagram showed ‘YES’ > “NO” Answers. It was concluded that the students’ responses of teaching speaking using picture series in Instagram were good.